PENGARUH RASIO LIKUIDITAS, RASIO RENTABILITAS DAN RASIO SOLVABILITAS TERHADAP NILAI PERUSAHAAN DENGAN PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY DAN GOOD CORPORATE GOVERNANCE SEBAGAI VARIABEL PEMODERASI (STUDI EMPIRIS PADA PERUSAHAAN MANUFAKTUR TERGOLONG RAWAN PENCEMARAN DI BURSA EFEK INDONESIA TAHUN 2009 – 2013) - Lara, Rahmi; Kamaliah, Kamaliah; Desmiyawati, Desmiyawati (Fakultas Ekonomi dan Bisnis, Universitas Riau, 2015)
Based on the description of the background of the problem, then that becomes aproblem in this research is how the simultaneous and partial effect betweencurrent ratio, Return on Assets and Debt to Equity Ratio Disclosure Of CorporateValues with Corporate Social Responsibility and Good Corporate Governance Asa moderating variable in the Manufacturing Company category in Prone topollution in the Indonesia Stock Exchange Year 2009 to 2013.The study population was all companies listed on the Jakarta Stock Exchange andclassified in an industry vulnerable to environmental pollution. Based on thepriority, then the company is classified as pollution-prone sectors: (1) Mining, (2)and Chemical Industry Association, (3) Automotive, and (4) Textiles. Based on theindustrial sector, the company acquired as many as 193 companies. Forsampling, the criteria used. Based on these criteria, then obtained a sample of 34companies manufacturing environments prone between the period 2009-2013.From the results of the partial test of the value of the company ROE known thatROE has no effect on the value of the company. These results support the researchconducted by Herdiana (2003), Wibowo (2005), Saso and Wulandari (2006) thatthere is no influence between ROE and the value of the company. From the testresults it is known that the disclosure of CSR does not affect the relationshipbetween financial performance and corporate value. These results support theresearch Hidayat (2010). In theory, the disclosure of CSR should be aconsideration of the investor before investing, because it contains socialinformation that has been done by the company. ROE and KM interactionvariables have an inverse relationship.The survey results revealed that as the increase in KM, then the relationship ROEand Tobins will decrease. It supports research Demsetz (1983), Fama and Jensen(1983) showed that in a certain stage, the level of managerial ownership is notalways positively linearly related loss of credit for the value of the company.